The Relationship between Hoax Behavior and Toxic Disinhibition among Indonesian High School Students - Achmad Fauzi Matondang; Afdal Afdal (Journal of Educational, Health and Community Psychology, 2023)
This research is motivated by the phenomenon of many students engaging in toxic behavior on the internet, so it needs to be investigated more deeply to gain a comprehensive understanding of this issue. The purpose of this research is to examine (1) the description of toxic disinhibition behavior (2) the description of hoax behavior among students in Indonesia, and (3) to test the relationship between hoax behavior and toxic disinhibition behavior. The research method used is a quantitative cross-sectional approach. The research sample consists of 600 students from seven provinces in Indonesia, selected using purposive sampling techniques. The research instruments used are tested scales for hoax behavior and toxic disinhibition. The data is analyzed using simple regression with the assistance of SPSS version 25.00. The findings of the research indicate that hoax behavior is correlated with toxic disinhibition. This research implies that students need to gain insights into healthy and productive online activities to prevent them from engaging in toxic behavior on the internet.